Exploring the effects of verb and noun treatment on verb phrase production in primary progressive aphasia: A series of single case experimental design studies. Issue 6 (3rd July 2022) - Taylor-Rubin, Cathleen; Nickels, Lyndsey; Croot, Karen
ABSTRACT: Evidence of generalization to connected speech following lexical retrieval treatment in Primary Progressive Aphasia (PPA) is scarce. Consequently, this study systematically investigated changes in verb phrase production following lexical retrieval treatment in a series of single case experimental design studies. Four individuals with PPA (three semantic- and one logopenic variant PPA) who had previously demonstrated that they could integrate verbs and nouns into sentence structures in a cueing paradigm, undertook a sequence of verb and noun lexical retrieval treatments using Repetition and Reading in the Presence of a Picture. Production of treated nouns- and/or verbs-in-isolation significantly improved following treatment for three of the four participants. Verb phrase production did not improve for one of these participants (logopenic PPA), perhaps due to the relatively small treatment dose. Two participants (semantic variant PPA) did, however, demonstrate across-level generalization, with improvement in treated verbs and using those verbs in (untreated) verb phrases. Their verb phrase production improved most after lexical retrieval treatment for both nouns and verbs, suggesting this combined approach may benefit across-level generalization for some individuals in clinical practice.